1970
DOI: 10.1002/bjs.1800570711
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal noxythiolin in faecal peritonitis

Abstract: Noxythiolin is a simple chemical compound which undergoes slow decomposition to liberate free formaldehyde. It is relatively non-toxic when given intraperitoneally to animals and has a high therapeutic ratio. When a lethal Gram-negative peritonitis has been induced in guinea-pigs with Proteus and coliform organisms, intraperitoneal injection of noxythiolin offers significant protection. In humans with faecal peritonitis, the use of noxythiolin intraperitoneally reduces the morbidity and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 16 publications
0
29
0
2
Order By: Relevance
“…They found that significantly more rabbits died which were receiving 5 ml of 2-5% or 10% noxythiolin solutions than those receiving normal saline. Browne and Stoller (1970), on the other hand, found that noxythiolin (500 mg/kg body-weight) significantly reduced the mortality of guinea-pigs with bacterial peritonitis (P<0-001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that significantly more rabbits died which were receiving 5 ml of 2-5% or 10% noxythiolin solutions than those receiving normal saline. Browne and Stoller (1970), on the other hand, found that noxythiolin (500 mg/kg body-weight) significantly reduced the mortality of guinea-pigs with bacterial peritonitis (P<0-001).…”
Section: Discussionmentioning
confidence: 95%
“…Its popularity stems from the work of Stoller (1967) and Browne and Stoller (1970) who showed that noxythiolin significantly reduced the mortality rate of guinea-pigs with bacterial peritonitis. They also reported an impressive series of twenty-three patients with faecal peritonitis: there were only three deaths and two of these were due to pulmonary emboli.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended concentration of noxythiolin is 2.5 per cent (Browne, 1967;Stoller, 1967;Browne and Stoller, 1970;Leger et al, 1972;Pickard, 1972;Gue, 1974), and since there is a stoichoimetric relationship between the dose of antiseptic and the number of organisms present, it seems likely that the disparity between our results and those of Gilmore (1977) and Cleaver et al (1974) is due to the fact that the latter workers used doses well below the recommended levels. The same criticism also applies to the results reported by Stewart and Matheson (1978a, b), where the dose of noxythiolin used was less than half the recommended level while the dose of tetracycline was very high.…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, rats and mice are relatively resistant to induction of Gram-negative peritonitis (Burnett et al, 1957 ;Browne and Stoller, 1970). In 1964 Schumer et al used an injection of a known amount of Escherichiu coli into the peritoneal cavity of guinea-pigs.…”
Section: W King Et Al Discussionmentioning
confidence: 99%
“…Induction of peritonitis in animals by intraperitoneal injection of bacterial suspension alone has proved to be difficult (Browne and Stoller, 1970). Furthermore, rats and mice are relatively resistant to induction of Gram-negative peritonitis (Burnett et al, 1957 ;Browne and Stoller, 1970).…”
Section: W King Et Al Discussionmentioning
confidence: 99%